Discourse Analysis as a Means to Scrutinize REDD+: An Issue of Current Forest Management Debate of Nepal (Journal of Forest and Livelihood, 2016)
This article shows how discourse analysis can be a methodological tool to scrutinize texts under the aegis of Reducing Emissions from Deforestation and Forest Degradation, sustainable management of forest, and conservation and enhancement of carbon (REDD+). A discourse is a perspective of an individual or an organization, which always tries to achieve a dominant position in the society. Texts used in discourses are impossible to understand properly in isolation. They are the reflections of social practices. Discourses, which contain multiple meanings, are also used as devices to make texts meaningful in regular communication. Analysis of discourses is called discourse analysis. Laclau and Mouffe (1985) believe that social structures (norms, rules and institutions) are created by pre-existing discourses of society, thereby we humans conceive objective reality according to the existing discourses. Alternatively, Fairclough (1995) believes that discourses not only reflect social structure but are also bounded by them. Both perspectives have been used as methodologies to analyse discourses, nonetheless Fairclough’s discourse analysis is more pragmatic than Laclau and Mouffee’s. The term ‘REDD+’ implies a discourse about forming new forestry institution in developing countries like Nepal, which is articulated in the name of mitigating deteriorating climate of the world. We suggest combining both perspectives to scrutinize the issue like REDD+. We found that discourse analysis is a suitable method to scrutinize REDD+ in the Nepalese context where people consider forest as a vital source of earning livelihoods and the foundation of sustaining local environment.Journal of Forest and Livelihood 13(1) May, 2015, page: 44-55